Innovation and Collaboration for Inclusive Sustainable Development: A Thematic Analysis of Social-Political Research Groups - Wahyunengseh, Rutiana Dwi; Suharto, Didik Gunawan; Abisono, Firya Qurratu'ain; Sunesti, Yuyun; Hastjarjo, Sri; Sandria, Andriko (Universitas Sebelas Maret, 2025)
The background of this study is the complex challenges of sustainable development in the era of globalization and digitalization, which require innovative solutions through cross-sectoral collaboration. The research problem centers on how the research ideas of Research Groups at FISIP Universitas Sebelas Maret contribute to transforming innovation and collaboration to strengthen policies and governance for sustainable development. This study aims to explore the transformation of innovation and collaboration in the context of sustainable development based on a thematic analysis of various research conducted by research groups in the Faculty of Socialand Political Sciences at Universitas Sebelas Maret. The main focus is to identify and analyze how technological innovation, community empowerment, and good governance contribute to development goals. Thematic analysis from Social and Political Research Groups was used, involving data collection through document analysis. The findings indicate that integrating digital technology, enhancing digital literacy, and adaptive governance are crucial for promoting inclusive and sustainable development. Additionally, collaboration among various stakeholders, both locally and internationally, has proven to be effective in addressing environmental and socialchallenges. Social and Political Research Groups have also highlighted the importance of cultural preservation in maintaining local identity and fostering community participation in development. Practical and strategic recommendations are provided for governments, educational institutions, and communities to implement effective innovation and collaboration to achieve development goals. The theoretical contribution of this research adds examples of research outcomes usingthematic analysis from collections of studies in specific academic fields.